Generation of Pulsed Laser Radiation at 1002 nm with a Quantum Defect of 2.6% - Xiaodan Dou; Lisha Wang; Yanjun Ma; Wenjuan Han; Honghao Xu; Degao Zhong; Bing Teng; Junhai Liu (IEEE Photonics Journal)
Low-quantum-defect pulsed oscillation at 1002 nm was achieved with a Yb:LuPO4 miniature crystal rod laser longitudinally pumped by a 976-nm diode laser, with a GaAs semiconductor saturable absorber to induce passive Q-switching. With 17.2 W of pump power absorbed in the crystal rod, an average output power of 0.85 W was generated at a repetition rate of 3.7 kHz, the resulting pulse energy, duration, and peak power were 230 μJ, 5.5 ns, and 41.8 kW, respectively.